Analisis Sistem Kemitraan Peternakan Ayam Broiler di Nagari Sungai Duo Kabupaten Dharmasraya Menurut Etika Bisnis Islam - Sumbara, Oka Liswan; Zuwardi, Zuwardi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This research is motivated by the existence of power inequality in the partnership system that exists between breeders and partner companies, unilateral policy making and a negative impact on breeders. The purpose of this study was to determine the analysis of the broiler farming partnership system in Nagari Sungai Duo according to Islamic business ethics. The type of research used is field research with a descriptive qualitative approach. Sources of data used in this study are primary data and secondary data with research informants livestock owners. Data collection techniques using interviews, observation and documentation. Data analysis techniques used include data reduction, data presentation and drawing conclusions. The results of this study indicate a partnership system between breeders and partner companies using a plasma nucleus pattern. The company acts as the core which has the role of providing production facilities, conducting coaching, controlling, scheduling, control and pricing agreements and marketing. While breeders as plasma provide stables complete with equipment and operational support equipment and focus on maintaining production facilities. The profit sharing system is determined by agreeing on a contract price at the beginning of the period, including sapronak and live chicken prices. The total sales/harvest of chickens based on the agreed contract price minus the total purchases of sapronak from the company, the result is the farmer's income. In a review of Islamic business ethics based on 5 principles including Unity, Equilibrium, Free wil, Responsibility and Benevolance, the partnership system that exists between breeders and partner companies is not fully in accordance with Islamic business ethics. The partnership system is not in accordance with the principles of Unity, Equilibrium, free will and benevolence.Keywords: Breeder, Islamic Business Ethics, Partnership System